A "step-ramp-step" protocol to identify running speed and power associated with the maximal metabolic steady state - Van Rassel, C. R.; Ajayi, O. O.; Sales, K. M.; Azevedo, R. A.; Murias, J. M.; Macinnis, M. J. (Medicine & Science in Sports & Exercise, 2023)
Purpose A previously established Step-Ramp-Step (SRS) exercise protocol was able to accurately predict the work rate associated with the maximal metabolic steady state (MMSS) in cyclists. The purpose of this study was to determine whether a modified SRS protocol could predict the running speed and power associated with the MMSS.